Synthesis of Ti3C2 mxene through in situ hf and direct hf etching procedures as electrolyte fillers in dye-sensitized solar cell - Adibah, N.A. (Trans Tech Publications Ltd, 2021)
MXene is the new family of two-dimensional (2D) transition metal carbides, carbonitrides and nitrides discovered in 2011. The unique properties of 2D MXene such as excellent mechanical properties, hydrophilic surfaces and metallic conductivity made it interesting for application in electrodes of rechargeable batteries, supercapacitors, photocatalysts, catalysts, transparent conducting films, and flexible high-strength composites. The MXene can be synthesized through a selective etching process by using either in-situ HF (hydrofluoric acid) or direct HF methods. This study reports on the effect of the in-situ HF and direct HF etching procedures on the morphology of the synthesis Ti2C3 MXene using titanium aluminum carbide (Ti2AlC3) as precursor. The morphology and elements presence were evaluated by using variable pressure field emission scanning electron microscope (FESEM) and energy dispersion X-ray (EDX) spectroscopy analyses, respectively. The analysis shows that the MXene synthesized through the direct HF method was successfully delaminated compared to the in-situ HF procedures. Â© 2021 Trans Tech Publications Ltd, Switzerland.